Computational modeling of cerebral aneurysm formation - Framework for modeling the interaction between fluid dynamics, signal transduction pathways and arterial wall mechanics - Schmid, H; Watton, P; McCormick, M; Lanir, Y; Ho, H; Lloyd, C; Hunter, P; Ehret, A; Itskov, M (2008)
Many phenomenological models of cerebral aneurysm formation have been proposed. Such studies have focused on modeling the structural adaption of the arterial wall. However, further development is required to accurately represent the underlying mechanobiology during growth and remodeling processes. Here, we present a general framework for modeling the interplay of fluid dynamics, molecular signaling pathways and arterial wall mechanics. © 2009 Springer Berlin Heidelberg.